Dual integrals in non-linear fracture mechanics - Stolz, Claude (Vietnam Journal of Mechanics, 2009)
We propose a dual approach in fracture mechanics based on complementary energy. The analysis of the dissipation shows that the thermodynamical force associated with the evolution of a crack is an energy release rate, form of which depends on the presence or not of mechanical discontinuities. This energy release rate is given as an integral based on free or complementary energy. We analyse the invariance of such integrals and we discuss the obtained results in elastoplasticity